Improvement of neuropsychological and cognitive functions in older adults through transcranial vibroacoustic stimulation: a double blind, randomized, comparative trial - Bae, Jang-Han; Ha, Jae-Young; Choung, Jai Jun; Cho, Min-Woo; Oh, Byung-In; Lee, Kun Ho; Youn, Young Chul; Kim, SangYun; Song, Dong-Keun; Shin, Chang-Ho (Frontiers in Aging Neuroscience, 2025)
IntroductionCognitive impairments are critical global public health issues. Recent research has focused on developing non-invasive methods for cognitive enhancement with the potential to slow cognitive decline. This study aimed to explore the effects of transcranial vibroacoustic stimulation (tVAS) on neuropsychological and cognitive functions in older adults.MethodsThis double-blind, randomization, comparative trial applied tVAS at frequencies of 20 or 40 Hz for 30 min per day over an 8-week period using a novel tVAS device. Neuropsychological assessments, saliva cortisol levels, electroencephalography (EEG), and event-related potentials (ERP) were evaluated before and after the intervention.ResultsFollowing the tVAS intervention, total scores on the consortium to establish a registry for Alzheimer’s disease-Korean version (CERAD-K) 1 and 2 indicated a significant overall improvement in cognitive function in both the 20 and 40 Hz tVAS groups (p < 0.01 and p < 0.05, respectively). Center for epidemiologic studies depression scale (CES-D) scores after 40 Hz tVAS showed a significant reduction in depressive symptoms compared to baseline (p = 0.045), while no significant differences were observed in the 20 Hz group. Individual-level analyses showed that 40 Hz tVAS, but not 20 Hz, increased power across all EEG frequency bands and enhanced N100 and P200 ERP component amplitudes. Group-level comparisons revealed pronounced differences in the gamma band and a significant increase in P200 amplitude in the 40 Hz group.DiscussionIndividual-level EEG and ERP analyses suggest that 40 Hz tVAS enhances neural plasticity, and early-stage sensory processing efficiency. Group-level comparisons further support the successful induction of gamma entrainment, potentially promoting brain network synchronization and increased sensitivity to high-frequency auditory stimuli. While the 40 Hz tVAS intervention demonstrated potential cognitive and affective benefits with favorable safety characteristics, larger-scale studies are needed to confirm its clinical applicability.Clinical trial registrationhttps://cris.nih.go.kr/, identifier registration KCT0010055.